Peningkatan Produktivitas Produk Unggulan Kabupaten Jombang dari Anyaman Bambu melalui Community Service - Siti Zahro; Hany Mustikasari; Faizal Susilo Hadi; Tri Sagirani; Hedi Amelia Bella Cintya; Nugraha Nugraha; Citra Aisyah Luqman; Moriska Sinderela; Dharma Adhi Sutanto; Muhammad Abiyu Syafi (GUYUB: Journal of Community Engagement, 2024)
The cooperation between the Jombang Regency Government and the Community Service Team of the University of Surabaya identified target partners for bamboo-woven from micro, small, and medium enterprises (MSMEs) to develop their businesses at national and international levels. However, problems related to productivity and human resource capabilities are a priority to be resolved. To resolve this, the purpose is to provide assistance and renew technology to increase the productivity of Jombang Regency's superior products from bamboo through community service. The strategy carried out at the beginning was to conduct socialization. The next stage is implementing the community service program: training, assistance, and application of technology. The final stage is program evaluation. Meanwhile, the ABCD (Asset Based Community Development) method was chosen for this Community Service program. The results identified five components: Discovery, Dream, Design, Define, and Destiny. The assets and potentials owned by the target partners are infrastructure and human resources. The dream is to develop their businesses at national and international levels, to be able to meet the needs of community demand, and to innovate more modern products. The program design was grouped into four clusters: production, products, management, and marketing. Furthermore, the community service team together with one bamboo-woven partner determines the program activities: Increasing assets (bamboo cutting machines and thinning machines), increasing product diversity, increasing management capabilities, and increasing product promotion media. Finally, implementing program activities to increase machine assets and machine operation training, innovative product workshops, financial literacy training, and photographing bamboo woven products for components in the e-catalog. Finally, partners have bamboo-cutting and slicing technologies, digital administration, and innovative products. In conclusion, this Community Service program needs to be continued to achieve the Target Partners' desire to become MSMEs with national and international markets